Design curves for stiffened engineered timber wall systems: A verified analytical approach. (October 2020) - Orlowski, Kristopher; Kennedy, David
Highlights: Exact finite strip method and Wittrick-Williams algorithm was developed upon and applied. First time this analytical approach has been used in timber engineering in stiffened timber walls. Computational cost efficiency is thousands of times greater than that of corresponding FEMs. Mathematical modelling has facilitated the creation of a set of simple and versatile design curves. Validation through experimental testing and finite element analysis was taken. Abstract: This manuscript introduces the mathematical modelling of efficient stiffened engineered timber wall systems and presents a collection of corresponding design curves. An analytical approach via the exact finite strip method through the Wittrick-Williams algorithm was used in this study to understand and predict the behaviour of such systems. Appropriate orthotropic material models and strength limits have been incorporated into the analytical method for the engineered timber panel and sawn cut timber stud stiffeners respectively. This is the first time that this approach has been used in this field of timber engineering and hence was verified through experimental testing and detailed Finite Element Analysis (FEA). Compared to FEA there is over a thousand-fold decrease in computational cost which allowed many parameters to be varied incrementally including: the thickness of the panel, number of stiffeners, height of the wall and applied load. The results of which has enabled a set of versatile and simple validated design curves to be developed and presented. With these design curves, for a desired load capacity, the optimal system configurations are given. Likewise, for a chosen configuration the allowable axial load is given.